Population Genetics and Phylogeography of Galapagos Fur Seals - Chaves, Jaime A.; Lopes, Fernando; Martínez, Daniela; Cueva, Dario F.; Gavilanes, Gabriela I.; Bonatto, Sandro L.; de Oliveira, Larissa Rosa; Páez-Rosas, Diego (Frontiers in Genetics, 2022)
Pinnipeds found across islands provide an ideal opportunity to examine the evolutionary process of population subdivision affected by several mechanisms. Here we report the genetic consequences of the geographic distribution of rookeries in Galapagos fur seals (GFS: Arctocephalus galapagoensis) in creating population structure. We show that rookeries across four islands (nine rookeries) are genetically structured into major groups: i) a western cluster of individuals from Fernandina; ii) a central group from north and east Isabela, Santiago, and Pinta; and possibly, iii) a third cluster in the northeast from Pinta. Furthermore, asymmetric levels of gene flow obtained from eight microsatellites found migration from west Isabela to Fernandina islands (number of migrants Nm = 1), with imperceptible Nm in any other direction. Our findings suggest that the marked structuring of populations recovered in GFS is likely related to an interplay between long-term site fidelity and long-distance migration in both male and female individuals, probably influenced by varying degrees of marine productivity.